Synthesis and evaluation of a polydisulfide with Gd–DOTA monoamide side chains as a biodegradable macromolecular contrast agent for MR blood pool imaging. (11th January 2013) - Ye, Zhen; Wu, Xueming; Tan, Mingqian; Jesberger, Jack; Grisworld, Mark; Lu, Zheng‐Rong
Abstract : Macromolecular Gd(III)‐based contrast agents are effective for contrast‐enhanced blood pool and cancer MRI in preclinical studies. However, their clinical applications are impeded by potential safety concerns associated with slow excretion and prolonged retention of these agents in the body. To minimize the safety concerns of macromolecular Gd contrast agents, we have developed biodegradable macromolecular Gd contrast agents based on polydisulfide Gd(III) complexes. In this study, we designed and synthesized a new generation of the polydisulfide Gd(III) complexes containing a macrocyclic Gd(III) chelate, Gd–DOTA monoamide, to improve the in vivo kinetic inertness of the Gd(III) chelates. (N6 ‐Lysyl)lysine‐(Gd–DOTA) monoamide and 3‐(2‐carboxyethyldisulfanyl)propanoic acid copolymers (GODC) were synthesized by copolymerization of (N6 ‐lysyl)lysine DOTA monoamide and dithiobis(succinimidylpropionate), followed by complexation with Gd(OAc)3 . The GODC had an apparent molecular weight of 26.4 kDa and T 1 relaxivity of 8.25 mm −1 s −1 per Gd at 1.5 T. The polymer chains of GODC were readily cleaved byl ‐cysteine and the chelates had high kinetic stability against transmetallation in the presence of an endogenous metal ion Zn 2+ . In vivo MRI study showed that GODC produced strong and prolonged contrast enhancement in the vasculature and tumor periphery of mice with breast tumor xenografts. GODC is a promising biodegradable macromolecular MRI contrast agent with high kinetic stability for MR blood pool imaging. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A polydisulfide containing Gd–DOTA monoamide side chains, GODC, was synthesized and evaluated as a biodegradable macromolecular MRI contrast agent with high kinetic stability. The chelates in the agent were highly stable against transmetallation with Zn 2+ ions and the polymer chains were readily reduced by endogenous thiols to facilitate the excretion of the agent. The agent produced strong and prolonged contrast enhancement in the vasculature and tumor periphery of mice bearing breast cancer xenograft.